Modélisation de l’érosion hydrique des sols sur un bassin versant du sud-ouest de Madagascar, le Fiherenana - Evelyne Payet; Pascal Dumas; Gwenaëlle Pennober (VertigO)
Worldwide, 70 % of coastal areas are undergoing shore line recession. Madagascar’s western coast is in sharp contrast, since accretion there is more pronounced than coastal recession process. One of the causes of coastal accretion is continental sediments, raising the problem of erosion on watersheds. Since the 1980’s, the Reef Complex of Toliara has been considered to be markedly degraded, due to the coral smothering of its structure by terrigenous materials originating from the Fiherenana river. In considering the problem of erosion process on the Fiherenana drainage basin, an approach based on computer modeling is proposed in this article, using the USLE model (Universal Soil Loss Equation), a model derived from the Universal Soil Loss Equation – USLE. This model is one of the most commonly applied for assessing sheet and rill erosion. USLE is widely used on various areas and at different scales. It takes into account four determining factors, such as soil erodibility, rainfall, slope length and steepness, land cover and conservation practice factor. This study is in line with the practice of Integrated Coastal Zone Management and aims at providing knowledge on erosion potential on the Fiherenana catchment, with a view to assessing its contribution to the dynamics of coastal sedimentation.